Pengaruh Fasilitas, Citra Destinasi, dan Persepsi Harga Terhadap Kepuasan Wisatawan di Objek Wisata Air Terjun Dlundung Trawas Kabupaten Mojokerto - Laila Mufida; Achmad Yanu Alif Fianto; Abdul Halik (eCo-Buss, 2025)
Tourist satisfaction is a key factor in maintaining the sustainability of the tourism industry because it directly affects repeat visits and economic contributions to local communities. Dlundung Waterfall in Trawas District, Mojokerto Regency, as one of the leading natural tourist destinations, experienced a decline in visitor numbers of more than 50% in 2024 relative to the prior year. This condition necessitates a study of the factors that influence tourist satisfaction. In this study is conducted to investigate the impact of infrastructure, destination image, and price on visitor consumer welfare at Dlundung Waterfall. The approach utilizes a quantitative method with primary data were gathered using a questionnaire administered to 100 respondents using purposive sampling. Based on multiple linear regression analysis, the results demonstrate that facilities, destination image, and price have a significant effect on itourist satisfaction, both individually and jointly. Together, these three variables explain 66.3% of the change in touristi satisfaction. The results of this study are expected to serve as a guideline for destination management and policy makers to enhance the quality of natural tourism management and supporting the development of sustainable regional tourism.